2011
DOI: 10.1159/000327084
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic Calcinosis Cutis in a Child: Chemical Composition of the Calcified Deposits

Abstract: Idiopathic calcinosis cutis (CC) is a rare disease in a child. The chemical composition of the calcified deposits in idiopathic CC was first qualitatively and quantitatively examined using vibrational microspectroscopy via spectral diagnosis. The combined application of the Fourier transform infrared (FT-IR) and Raman microscopic techniques was used to detect and identify the nature of the components of the calcified deposits in idiopathic CC and to compare the results with histopathological findings. Two majo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 38 publications
0
9
0
1
Order By: Relevance
“…The combination of techniques has revealed the most specific information on the composition of the deposits . The two major components in human idiopathic CC of subcutaneous tissues are type B carbonated apatite and β‐carotene . In future studies, it may be prudent to perform Raman spectroscopy to determine whether β‐carotene is also a component of CC in canine skin.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of techniques has revealed the most specific information on the composition of the deposits . The two major components in human idiopathic CC of subcutaneous tissues are type B carbonated apatite and β‐carotene . In future studies, it may be prudent to perform Raman spectroscopy to determine whether β‐carotene is also a component of CC in canine skin.…”
Section: Discussionmentioning
confidence: 99%
“…In 2004, Bécuwe et al (2) identified 17 prior cases of MICC, including 13 with Down syndrome, and added one additional patient without. At least four other cases have also been documented (3–6).…”
Section: Discussionmentioning
confidence: 99%
“…Fourier transform infrared spectroscopy is a measurement technique that can record infrared spectra. This method has been proven to yield rich information about foreign bodies in the skin . In the present case, the FTIR spectra obtained from the splinter‐shaped foreign body showed specific absorption of carbon, oxygen, phosphorus, and calcium, indicating that the material was bone.…”
Section: Discussionmentioning
confidence: 55%